Parenting Training: Melihat Pengaruhnya Terhadap Gerak Mobilisasi Sendi Bagi Penyadang Cerebral Palsy di Kabupaten Malang - Sri Wahyuni; Klemensia Nini (Jurnal Pelayanan Pastoral, 2020)
The purpose of this study was to obtain data on the effect of parenting training on the joint mobilization of Cerebral Palsy children. The subject of his research was the parents of Cerebral Palsy children. Data collection techniques by observation and questionnaire. The instrument used in connection with this questionnaire method is a multilevel scale questionnaire. While the instrument for observation is in the form of a check list. The independent variable is parenting training (X) while the dependent variable is the increase in joint area (Y). The sample used is random sampling. This type of research is quantitative research. The research design is a correlational study. The type of relationship used in this study is a symmetrical relationship. The population is 25 people, while the sample is 23 people. In terms of data analysis, researchers look for and calculate the correlation coefficient between variables. The results obtained from this study are the magnitude of the relationship or effect of parenting training on the joint mobilization of Cerebral Palsy children by 25. So, the effect is at the level of "sufficient" 23 Percentage of results from sub-district. Singosari 73.4%, and sub-district Lawang at 67%.